Classroom Interaction of English as an Additional Language (EAL) in Primary Level at Canggu Community School: A Study Based on a Conversation Analysis Theory. Thesis. Language Education Departement, Postgraduate Program, Ganesha University of Education. - Astiti, Gusti Ayu Ketut (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Astiti Gusti Ayu Ketut (2012), Classroom Interaction of English as an Additional Language (EAL) in Primary Level at Canggu Community School: A Study Based on a Conversation Analysis Theory. Thesis. Language Education Departement, Postgraduate Program, Ganesha University of Education. This thesis has been approved by advisor I : Prof Dr Ni Nyoman Padmadewi, M.A and Advisor II: Prof. Dr. I Ketut Seken, M.A. Key words: classroom interaction, conversation analysis, turn-taking organization, sequence organization, repair organization This study analyzed the classroom interaction of English as an Additional Language (EAL) in Primary level at Canggu Community School. This study followed a qualitative description of case study which uses Conversation Analysis to analyze the talk-in interaction in terms of turn-taking organization, sequence organization and the repair organization. The subjects of the study were an EAL teacher and EAL students who come from different classrooms in Primary level. The methods of data collection in this study were audio and video recording of classroom interaction, observation and interview with the teacher. The data of this study were obtained from the five lessons of five different groups. The main data were in the form of classroom interaction transcriptions.Â  This study revealed that in terms of turn-taking organization, the personal solicit was the dominant solicit that occurred and the general solicit was the least dominant. The study also revealed that students made self-selections to take a turn. In terms of the sequence organization, the most common classroom interaction that occurred was Initiation-Response-Feedback (IRF)âsequence where the talk was initiated by the teacher and also by the students. In terms of the repair organization, other-initiated other-repair (OIOR) was the dominant type of repair that occurred in these EAL groups, in which most of the repairs were made by the teacher without giving much chance to the students to uptake the repair after the teacher. Based on the result of this study, it was concluded that in classroom interaction, how the turn-taking, sequence and repair were organized were vital components to enhance the learning of EAL students to improve their English proficiency and could increase their confidence in the classroom by having more chance to take a turn in discussion and also initiated the topic and conversation. Besides that the students need to have more opportunities to uptake the correct language after the repairs from the teacher. ABSTRAK Astiti Gusti Ayu Ketut (2012). Interaksi Kelas pada Pembelajaran Bahasa Inggris sebagai Bahasa Tambahan Tingkat Dasar di Canggu Community School: Studi dengan Menggunakan Analisis Percakapan. Tesis. Departement Pendidikan Bahasa, Pasca Sarjana, Universitas Pendidikan Ganesha. Tesis ini sudah disetujui dan diperiksa oleh: Pembimbing : Prof. Dr. Ni Nyoman Padmadewi, M.A. dan Pembimbing II: Prof. Dr. I Ketut Seken, M.A. Kata-kata kunci: interaksi kelas, percakapan analisis, organisasi mengambil giliran, organisasi rangkaian, organisasi perbaikan Studi ini fokus pada interaksi kelas pada pembelajaran Bahasa Inggris sebagai bahasa tambahan pada tingkat dasar (English as an Additional Language)-EAL di Canggu Community School. Ini merupakan studi kasus dengan pemaparan kualitatif. Subjek dari penelitian ini adalah seorang guru EAL dan para siswa EAL yang berasal dari lima grup. Penelitian ini menggunakan Analisis Percakapan (Conversation Analysis) dalam menganalisis data. Data penelitian didapatkan dari rekaman video dan suara interaksi kelas, observasi dan melakukan wawancara dengan guru EAL. Data utama berupa lima transkripsi percakapan dari lima kelas yang berbeda. Analisis data menunjukkan bahwa organisasi bergiliran (turn-taking organization) yang paling banyak muncul adalah guru menunjuk murid untuk mendapat kesempatan berbicara. Data tentang organisasi rangkaian interaksi (sequence organization) didapatkan bahwa guru lebih banyak memulai interaksi dan memperkenalkan topik pada siswa, tetapi topik dan inisiatif juga bisa dimulai dari siswa. Data tentang organisasi perbaikan (repair organization), menunjukkan bahwa kebanyakan perbaikan (repair) datangnya dari guru, di mana kurang kesempatan bagi siswa untuk memperbaiki kesalahan bahasa mereka. Dari analisis data dan pembahasan, dapat disimpulkan bahwa di dalam interakasi kelas guru seharusnya lebih banyak memberikan kesempatan siswa untuk berusaha aktif sendiri yang mana di dalam studi ini guru berusaha memberikan kesempatan yang sama kepada setiap siswa untuk berbicara dengan cara menunjuk siswa. Demikian juga halnya dalam rangkaian interaksi dan pengaturan perbaikan kesalahan, dengan adanya kesempatan bagi siswa memulai berinteraksi lebih banyak dan mendapat kesempatan dalam memperbaiki kesalahan bahasa diharapkan dapat meningkatkan kemampuan penggunaan bahasa Inggris mereka.